Performance study on modified asphalt cement using Trinidad Lake Asphalt (TLA) as a polymer modifier - Ramlal, Shiva; Clark, Amy; Ramjattan-Harry, Vitra; Maharaj, Rean (Universiti Teknologi MARA, Sarawak, 2025)
Asphalt binders play a crucial role in pavement performance by providing the necessary viscoelastic properties to withstand traffic loads and environmental stressors. This study investigates the rheological characteristics of Trinidad Lake Asphalt (TLA) blended with penetration grade (PEN 60/70 and PEN 160/220) binders to assess suitability for road applications. Using the Dynamic Shear Rheometer (DSR) test, this study evaluates efforts on varying TLA concentrations as influencing key parameters such as complex shear modulus (G*) and phase angle (δ) across different temperatures and frequencies. The results demonstrate that increasing TLA content enhances rutting resistance by increasing stiffness, but it also impacts fatigue resistance. These findings contribute to the optimisation of asphalt formulations for improved pavement performance under diverse traffic and climatic conditions.